2011
DOI: 10.1007/s11665-011-9870-y
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion Bonding of Stainless Steel to Copper with Tin Bronze and Gold Interlayers

Abstract: Vacuum diffusion bonding of stainless steel to copper was carried out at a temperature ranging from 830 to 950°C under an axial pressure of 3 MPa for 60 min with three kinds of interlayer metals: tin-bronze (TB) foil, Au foil, and TB-Au composite interlayer. The results showed that the grain boundary wetting was formed within the steel adjacent to the interface due to the contact melting between TB and Au when TB-Au composite interlayer was used. The grain boundary wetting could occur at a relatively low tempe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 12 publications
(3 reference statements)
0
12
0
1
Order By: Relevance
“…Copper-SS joints have been produced by using various solid state or fusion welding processes. Solid state welding processes like diffusion welding, friction stir welding (FSW), and explosive welding have been extensively used [3][4][5][6][7][8]. In diffusion welding of copper-SS, the interlayer material, applied temperature, and pressure, etc.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Copper-SS joints have been produced by using various solid state or fusion welding processes. Solid state welding processes like diffusion welding, friction stir welding (FSW), and explosive welding have been extensively used [3][4][5][6][7][8]. In diffusion welding of copper-SS, the interlayer material, applied temperature, and pressure, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Xiong et al [6] reported that compared to pure tin, bronze or gold, use of tin-bronze-gold composite interlayer, allowed the use of comparatively lower bonding temperature, increased grain boundary wetting and tensile strength. Imani et al [7] for FSW of copper-SS joints reported that off-setting of the pin toward copper side by 30% produced defect free welds with better tensile strength. Shanjeevi et al 2016 [8] reported that friction pressure is the most significant process parameter of FSW followed by pin rotational speed affecting the resultant microstructure and tensile properties of copper-SS joints.…”
Section: Introductionmentioning
confidence: 99%
“…This in itself is not too impressive given the data from Yilmaz [171] discussed earlier. Besides, Xiong et al [173] reached UTS of 228 MPa using TLP bonding (without pressure variation) with a 100 µm thick Tin-Bronze (Alloy QSn 6.5~0.1: wt% 6-7 Sn, ≤ 0.3 Zn, 0.1-0.25 P, ≤0.05 Fe, ≤0.02 Pb, ≤0.002 Al, balance Cu) and a 5 µm Au interlayer. Yuan et al [50] further used a Gleeble 1500 thermo-mechanical material testing system.…”
Section: Diffusion Bonding and Tlp Bonding Of 304 And 316 To Cu And C...mentioning
confidence: 99%
“…The optimum conditions observed for this work were at 850 C • to get tensile strength of 228 Mpa for Tb-Au interlayer. The microstructure of joint was examined using SEM and EDS [9]. Sabetghadam (2010) evaluated the microstructure of diffusion bonded joint between stainless steel 410 and copper using Ni as interlayer.…”
Section: Introductionmentioning
confidence: 99%